Book Review: Unf*ck Your Worth: Overcome Your Money Emotions, Value Your Own Labor, and Manage Financial Freak-Outs in a Capitalist Hellscape - Courtney Fraser Regan (Journal of Financial Therapy, 2024)
Book Review